2018
DOI: 10.12816/0044689
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Public Knowledge regarding the Differences between Hyperthyroidism and Hypothyroidism

Abstract: Background: Thyroid hormones play a pivotal role in the metabolism of human body. Changes of the thyroid gland activity manifest in nearly all body systems. Appropriate knowledge of the public about thyroid disorders and their manifestations is essential for early detection. Objective: The aim of this study was to assess public knowledge regarding the differences between hyperthyroidism and hypothyroidism in Tabuk city, Saudi Arabia. Methods: A cross sectional study was conducted on 300 randomly selected adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
1
11
2
Order By: Relevance
“…According to a survey in Tabuk-City, 52 percent of respondents had strong knowledge, while 45% had inadequate knowledge, similar to the findings of a study in Riyadh about the thyroid-gland and its disorders (Alhawiti et al, 2018). In Malaysia, paper among 288 women in Selangor; found nearly half (51.7%) women have-good-knowledge regarding thyroid disorder and 48.3% of women have poor knowledge (Mohamed et al, 2020).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…According to a survey in Tabuk-City, 52 percent of respondents had strong knowledge, while 45% had inadequate knowledge, similar to the findings of a study in Riyadh about the thyroid-gland and its disorders (Alhawiti et al, 2018). In Malaysia, paper among 288 women in Selangor; found nearly half (51.7%) women have-good-knowledge regarding thyroid disorder and 48.3% of women have poor knowledge (Mohamed et al, 2020).…”
Section: Resultssupporting
confidence: 52%
“…However, manifestations of hypothyroidism were recognized by a lower percentage of respondents (Almuzaini et al, 2019). In Tabuk city, Alhawiti et al, (2018) found that the knowledge of the respondent's regards symptoms of hyperthyroidism was poor as only half the respondents roughly identified the common manifestations of the disease. The intolerance to hot weather and menstrual disturbances with hyperthyroidism were the least identified (50.7% and 44.3%).…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
See 1 more Smart Citation
“…According to a study conducted in Tabuk city, the knowledge percent was close to our results which were 52% of respondents having good knowledge, while 45% have poor knowledge about the thyroid gland and its disorders. Good knowledge was demonstrated in questions on the type of thyroid gland (endocrine; by 71.4% of respondents), and the most susceptible individuals to have disorders were women; by 90.4% of respondents [13]. Another Saudi study in Hail reported that, only 6.6% among the participants did not know what the thyroid gland is, while 93.4% have chosen specific answers that are facts regarding the thyroid on different levels of knowledge [14].…”
Section: Table 5 Relationship Between Knowledge and Sociodemographic Features Of The Participantsmentioning
confidence: 99%
“…Taif city, it's a city of Saudi Arabia and considered high altitude area because it is the elevation is 2,000 meters above sea level. In high altitude areas, the hypoxia changes the level of thyroid hormones T3 & T4 (Alhawiti et al, 2018). Thus according to this research, high altitude places create hypoxia, which must be compensated for by mild hyperthyroidism (Barnholt et al, 2006).…”
Section: Introductionmentioning
confidence: 69%